Ethylene (co) oligomerization using iminopyridyl Ni(II) and Pd(II) complexes bearing benzocycloalkyl moieties to access hyperbranched ethylene oligomers and ethylene-MA co-oligomers - Ding, Beihang; Chang, Guanru; Yan, Zhengpeng; Dai, Shengyu (Frontiers in Chemistry, 2022)
Hyperbranched ethylene oligomers and polar functionalized co-oligomers synthesized via ethylene chain walking (co)oligomerization is a very attractive strategy. In this study, a series of dibenzhydryl iminopyridyl ligands with benzocycloalkyl and naphthyl moieties and the corresponding Ni(II) and Pd(II) complexes were synthesized and characterized. The Ni(II) complexes were highly effective in ethylene oligomerization and ethylene oligomers with hyperbranched microstructures were generated from this system. The corresponding Pd(II) complexes showed moderate oligomerization activities in ethylene oligomerization and hyperbranched ethylene oligomers were also yielded from the system. More significantly, the Pd(II) complexes can also effectively promote the co-oligomerization of ethylene with methyl acrylate (MA) to obtain hyperbranched polar functionalized ethylene-MA co-oligomers. The reaction temperature, catalyst ligand structure and metal type all have significant effects on ethylene (co)oligomerization with respect to catalytic activity, molecular weight and topology of the oligomers.